Long-term use of everolimus as a component of immunosuppressive therapy in liver transplant recipients - M. Sh Khubutia (Transplantologiâ, 2016)
This article presents a three-year experience with mTOR inhibitors in the schemes of immunosuppressive therapy in patients post liver transplantation.